ANALYSIS OF HOME OWNERSHIP FINANCING FOR ISLAMIC BANKS IN INDONESIA THROUGH SHARIA ASSET BACKED SECURITIES-PARTICIPATION LETTER - Suci Aprilliani Utami; Aneu Cakyaneu; Neni Sri Wulandari (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2020)
This research was conducted to find out the financing opportunities of home ownership financing for Islamic banks through Sharia Asset Backed Securities-Participation Letters (EBAS-SP) in Indonesia. EBAS-SP are asset backed securities that have a portfolio in the form of a participation letter for secondary home ownership financing that has a system that is in accordance with Islamic Sharia so that in each issuance process the securities must obtain a statement of Sharia principle conformity from the expert team Sharia capital market and Sharia Supervisory Board. This study uses the Analytic Hierarchy Process (AHP) approach, following the priority of the strategy as a solution that can be offered. The results of this study indicate that: First, there are 4 issues of issues in developing the ability to mitigate the risk of home ownership financing for Islamic banks in Indonesia through the asset-backed effect of Islamic assets-participation letters, including legal / structural issues, sharia issues, operational issues and human resource issues. Second; For priority issues in terms of the use of Sharia Asset Backed Securities instruments and Participation Letters in the AHP Method frame according to the agreement of Experts, Practitioners, Academics and Regulators are operational aspects and aspects of human resources (HR). Third; the results of this study also show a picture of a solution in the strategy of increasing risk mitigation in PPR products through EBAS-SP for all four issues. And finally, the priority solution in solving problems based on expert agreement is the solution in legal / structural aspects, sharia aspects and operational aspects. So that the risk of home ownership financing mitigation using securities-backed securitization instruments can be a solution for home ownership financing for the community. Because EBAS takes the form of a participation letter supported by liquid assets and has a relatively small risk.